PREVENTIVE MEASURE FOR MARITAL RAPE THOUGHT THE QUR'AN - Shafira, Enno Farrisafina (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
Various statements state that marital rape is taboo, unnatural, irrational and rarely legitimized by religion. However, over time, marital rape has become a separate theme that has attracted the attention of many parties. In positive law in Indonesia, as in the 2004 Domestic Violence Law, marital rape is a part of domestic crime. There seems to be a difference between these two things, whereas in some literature it is stated that in fact marital rape does not really reflect the teachings of Islam. So the assumption that marital rape is not legitimized in religious terms is something that cannot be justified. Looking at this matter, this article aims to find out how the Al-Qur'an views preventing marital rape. This article describes how the Qur’an enlightens Muslims by explaining proper ethics both in everyday life and in sexual activities. This is actually an effort to prevent marital rape in the Qur’an.